A medicalização da educação e da resistência no presente: disciplina, biopolítica e segurança - LEMOS, Flávia Cristina Silveira (Universidade Federal do Pará, 2017)
This article aims at bringing to debate nowaday´s intensive medicalization of existence, especially when it occurs by silencing of resistance by both disciplines and biopolitical and also by the strategies of increasingly refined security. These are used tactically, in a set of institutions that are run by expert specialists in diagnosing social deviations and differences by biomedical rationales, psychologizing and pathologizing of inventive education and political dissent. Our aim in this work is to problematize these everyday social practices and their effects. We also propose to describe and analyze the resistance to these practices. To sustain our argument we have the theoretical support of Michel Foucault and Robert Castel . This study is part of and ongoing research and historical nature through which we intent to contribute to the critique of medicalization of education and political dissent, today, in a society of security.